Enhancing Halal Supply Chain Resilience through Digital Traceability: A Multi-Stakeholder Perspective - Fajar Azhari Julian; Novianti Rachmayani; Abdul Rochim; Andri Mulyana; Rachmat Darmawan; Ahmad Maulidizen (CV. ALIM'SPUBLISHING, 2026)
The increasing complexity of global halal supply chains has created significant challenges in maintaining integrity, transparency, and resilience across interconnected stakeholders. Disruptions caused by technological limitations, information asymmetry, regulatory differences, and trust issues can threaten halal compliance and consumer confidence. This study aims to examine how digital traceability mechanisms contribute to enhancing halal supply chain resilience from a multi-stakeholder perspective. Using a qualitative conceptual approach based on an integrative literature review, this study synthesizes insights from halal supply chain management, digital transformation, organizational resilience, and industrial psychology. The findings indicate that digital traceability improves supply chain resilience through three key mechanisms: strengthening information transparency, increasing stakeholder trust, and facilitating collaborative decision-making. However, technological adoption alone is insufficient; successful implementation requires psychological readiness, organizational commitment, digital competency, and trust-based relationships among stakeholders. From an industrial psychology perspective, employee acceptance, perceived usefulness, organizational support, and cross-functional collaboration represent critical determinants influencing digital traceability effectiveness. This study contributes to the halal supply chain literature by integrating technological and behavioral perspectives, emphasizing that resilient halal ecosystems require alignment between digital infrastructure and human-centered organizational practices. The findings provide practical implications for halal industry managers, policymakers, and certification authorities in designing sustainable and adaptive halal supply chain systems.